Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Feminism and ecological communities: an ethic of flourishing - Cuomo, Chris J. (Routledge, 1998)
Feminism and Ecological Communities presents a bold and passionate rethinking of the ecofeminist movement. It is one of the first books to acknowledge the importance of postmodern feminist arguments against ecofeminism whilst persuasively preseenting a strong new case for econolocal feminism. Chris J.Cuomo first traces the emergence of ecofeminism from the ecological and feminist movements before clearly discussing the weaknesses of some ecofeminist positions. Exploring the dualisms of nature/culture and masculing/feminine that are the bulwark of many contemporary ecofeminist positions and questioning traditional traditional feminist analyses of gender and caring, Feminism and Ecological Communities asks whether women are essentially closer to nature than men and how we ought to link the oppression of women, people of colour, and other subjugated groups to the degradation of nature. Chris J.Cuomo addresses these key issues by drawing on recent work in feminist ethics as well as teh work of diverse figures such as Aristotle, John Dewey, Donna Haraway adn Maria Lugones. A fascinating feature of the book is the use of the metaphor of the cyborg to highlight the fluidity of the nature/culture distinction and how this can enrich econfeminist ethics and politics. An outstanding new argument for an ecological feminism that links both theory and practice, Feminism and Ecological Communities bravely redraws the ecofeminist map. It will be essential reading for all those interested in gender studies, environmental studies and philosophy.
Keywords: approches et analyses; com5170; cours; discipline; environnement; philosophie; postmodernisme; premier cycle; sciences humaines; thématiques; écoféminisme

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art